2019
DOI: 10.1080/13696998.2019.1580713
|View full text |Cite
|
Sign up to set email alerts
|

Cost-impact of cardiac magnetic resonance imaging with Fast-SENC compared to SPECT in the diagnosis of coronary artery disease in the U.S

Abstract: Aims: The purpose of this study is to assess the economic cost differences and the associated treatment resource changes between the developing coronary artery disease (CAD) diagnostic tool fast strain-encoded cardiac imaging (Fast-SENC) and the current commonly used stress test single-photon emission computed tomography (SPECT). Materials and methods: A "payer perspective" model was created first, consisting of long-term and short-term components that used a hypothetical cohort of patients of average age (60.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…A systematic review analysis showed that sensitivity for stress echocardiography can be variable between %53 and %91 and speci city between %44 and %94 [36]. sensitivity and speci city for SPECT reported %70 and %76 respectively [37]. However, another study showed that sensitivity and speci city of SPECT in CAD diagnosis was %83 and %89 [38].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review analysis showed that sensitivity for stress echocardiography can be variable between %53 and %91 and speci city between %44 and %94 [36]. sensitivity and speci city for SPECT reported %70 and %76 respectively [37]. However, another study showed that sensitivity and speci city of SPECT in CAD diagnosis was %83 and %89 [38].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review analysis showed that sensitivity for stress echocardiography can be variable between %53 and %91 and speci city between %44 and %94 [35]. sensitivity and speci city for SPECT reported %70 and %76 respectively [36]. However, another study showed that sensitivity and speci city of SPECT in CAD diagnosis was %83 and %89 [37].…”
Section: Discussionmentioning
confidence: 99%
“…One key advantage of the proposed rapid exam is using SENC for fast strain measurements in only 6 seconds. A large body of literature showed the value of myocardial strain analysis for early detection of subclinical cardiac dysfunction in different cardiovascular diseases before global heart function is affected or symptoms of cardiovascular diseases are observed (28-30), especially in coronary artery disease (31) and heart failure (32), which would allow for early intervention and better outcomes. Further, besides providing strain measurements, SENC showed the capability of producing reproducible global function measurements that are in close agreement with those obtained from cine images (33-35).…”
Section: Discussionmentioning
confidence: 99%